The Effect Of Resistance Band Training On Arm Strength In Beginner Swimming Of The Garuda Laut Palopo Club - Hilda Sari; A. Heri Riswanto; Hikrawati Hikrawati; Rachmat Hidayat (STKIP Muhammadiyah Kuningan, 2023)
This study aims to determine the effect of resistance band training on arm strength in the beginner swimming of Garuda Laut Palopo Club. The method used in this study was an experimental method which consisted of 12 people as a sample. Data collection techniques used are observation and documentation. The type of data source used is the primary data source. The results of this study indicate that the average value (mean) of the pre-test is 48.2500, and the post-test is 59.7500. std. Deviation pre-test 3.84057 and post-test 3.04884. minimum value pretest 43.00 and posttest 55.00. maximum pretest value of 55.00 and posttest 66.00. Then the probability figure obtained from sig is 0.000 > 0.05, which means Ho is rejected. Thus, resistance band training significantly affects arm strength in beginner swimming at the Palopo Laut Garuda Club.